2012
DOI: 10.3390/f3020300
|View full text |Cite
|
Sign up to set email alerts
|

Using Silviculture to Influence Carbon Sequestration in Southern Appalachian Spruce-Fir Forests

Abstract: Enhancement of forest growth through silvicultural modification of stand density is one strategy for increasing carbon (C) sequestration. Using the Fire and Fuels Extension of the Forest Vegetation Simulator, the effects of even-aged, uneven-aged and no-action management scenarios on C sequestration in a southern Appalachian red spruce-Fraser fir forest were modeled. We explicitly considered C stored in standing forest stocks and the fate of forest products derived from harvesting. Over a 100-year simulation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…Since the function of forests as carbon sinks and sources is commonly accepted, there exist a plentitude of studies about forests and their role in the carbon cycle on a worldwide or continental level [13,14] and for managed [15,16] and unmanaged forests [17]. Furthermore, several studies on a regional [18][19][20][21] or national level [7,22] which include all climate change mitigation effects (often excluding soil carbon) are available as well as many experimental studies on a stand level [23,24]. However, the latter only partially contains the wood product sector and substitution effects.…”
Section: Introductionmentioning
confidence: 99%
“…Since the function of forests as carbon sinks and sources is commonly accepted, there exist a plentitude of studies about forests and their role in the carbon cycle on a worldwide or continental level [13,14] and for managed [15,16] and unmanaged forests [17]. Furthermore, several studies on a regional [18][19][20][21] or national level [7,22] which include all climate change mitigation effects (often excluding soil carbon) are available as well as many experimental studies on a stand level [23,24]. However, the latter only partially contains the wood product sector and substitution effects.…”
Section: Introductionmentioning
confidence: 99%
“…These contradictions may be due to the complexity of the calculations, as acknowledged by Moore et al. (), who emphasized that the accuracy of their results depended upon several factors, including the forest products that were generated. Nunery and Keeton () even showed that the comparison between even‐ and uneven‐aged silviculture is influenced by the level of structural retention applied in the treatments and also differs if carbon storage is considered instead of carbon sequestration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, two of the studies examined the total amount of carbon in the ecosystem very shortly after harvesting (Lee, Morrison, Leblanc, Dumas, & Cameron, ) instead of considering it over a full rotation (Nilsen & Strand, ). The most complete studies, based upon simulations (Moore, DeRose, Long, & van Miegroet, ; Nunery & Keeton, ; Pukkala, Lähde, & Laiho, ) or long‐term measurements (Nilsen & Strand, ), provide equivocal results in terms of the best silvicultural approach to sequester or store carbon. These contradictions may be due to the complexity of the calculations, as acknowledged by Moore et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tree carbon storage, for example, is now increasingly recognized as an important forest function and it has become a central point in climate change discussions [49,50]. Strong trade-offs among supply, regulation, and cultural ecosystem services have been identified and described [48,51,52].…”
Section: Relaxing and Expanding The Sustained-yield And Single-good Pmentioning
confidence: 99%